Mechanisms Underlying Enterococcus faecalis-Induced Tumor Necrosis Factor-α Production in Macrophages - Eun-Kyoung Choi; Dae-Eob Kim; Won-Mann Oh; Yun-Woong Paek; In-Chol Kang (International journal of oral biology, 2010)
Enterococcus faecalis, a gram-positive bacterium, has been implicated in endodontic infections, particularly in chronic apical periodontitis. Proinflammatory cytokines, including tumor necrosis factor-α (TNF-α), are involved in the pathogenesis of these apical lesions. E. faecalis has been reported to stimulate macrophages to produce TNF-α. The present study investigated the mechanisms involved in TNF-α production by a murine macrophage cell line, RAW 264.7 in response to exposure to E. faecalis. Both live and heat-killed E. faecalis induced high levels of gene expression and protein release of TNF-α. Treatment of RAW 264.7 cells with cytochalasin D, an inhibitor of endocytosis, prevented the mRNA up-regulation of TNF-α by E. faecalis. In addition, antioxidant treatment reduced TNF-α production to baseline levels. Inhibition of extracellular signal-regulated kinase (ERK) and p38 mitogen-activated protein (MAP) kinase also significantly attenuated E. faecalis-induced TNF-α expression by RAW 264.7 cells. Furthermore, activation of NF-κB and AP-1 in RAW 264.7 cells was also stimulated by E. faecalis. These results suggest that the phagocytic uptake of bacteria is necessary for the induction of TNF-α in E. faecalis-stimulated macrophages, and that the underlying intracellular signaling pathways involve reactive oxygen species, ERK, p38 MAP kinase, NF-κB, and AP-1.